Relationship between water structure and properties of poly(methyl methacrylate-b-2-hydroxyethyl methacrylate) by solid-state NMR. Issue 10 (13th August 2017) - Mochizuki, Akira; Miwa, Yuko; Miyoshi, Riko; Namiki, Takahiro
Abstract: We previously reported that the platelet compatibility of methyl methacrylate (MMA)–2-hydroxyethyl methacrylate (HEMA) diblock copolymers is related to the characteristic water structure in the copolymer, as the copolymer has an excess amount of nonfreezing water when compared with that estimated from the amounts of water in HEMA and MMA homopolymers. Thus, in this study, the relationship between water structure and polymer structure, including the heterogeneity and mobility of the copolymer, was investigated using differential scanning calorimetry (DSC) and nuclear magnetic resonance (NMR) spectroscopy. The prepared copolymers were classified into two groups: copolymers with a short, constant polyMMA segment length (Mn = ~2900) and copolymers with a constant polyHEMA segment length (Mn = ~9500), whereas the lengths of the counter segments varied. DSC analysis showed that when the polyMMA and polyHEMA segment lengths are similar, the amount of nonfreezing water increases, regardless of the total molecular weight of the copolymer. NMR analysis showed that heterogeneity of the copolymer is enhanced and the mobility of the copolymer decreases when the segment lengths are similar. These findings suggested that the excess amount of nonfreezing water is formed when the properties of water near the HEMA unit change from freezing to nonfreezing owing to interactions with the MMA unit. In addition, it is suggested that the heterogeneity of the copolymer structure or the mobility of the polymer are involved in the generation of excess nonfreezing water.